Effectiveness of computed tomography-guided nasotracheal intubation procedure on predicting tube advancement difficulty and preventing epistaxis: a prospective case-control study - Orbay Yasli, Seher; Gunay Canpolat, Dilek; Baydan, Ebru; Ahmet Emin Demirbas (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the effectiveness of computed tomography-guided nasotracheal intubation procedure in predicting tube advancement difficulty and preventing epistaxis. Methods: The prospective study was conducted at Erciyes University Faculty of Dentistry from April 2018 to June 2019 and comprised maxillofacial surgery patients of either gender aged 18-50 years who were due to undergo bimaxillary orthognathic surgery, which was defined as American Society of Anaesthesiology grade I or II. The space where the tube was to be passed in the internal nasal valve region was measured horizontally and vertically using computed tomography. A single experienced anaesthesiologists intubated all the patients who were later divided into ’easy’ group A and ’difficult’ group B on the basis of the effort required to advance the tube through the nasal passage. Data was analysed using JASP version 0.14.1.0). Results: Of the 60 patients, 42(70%) were females and 18(30%) were males. The overall mean age was 29.0±10.5 years and the mean body mass index value was 23.6±4.0kg/m2 (p>0.05). There were 28(46.6%) patients in group A, and 32(53.3%) in group B. Median distances were significantly shorter and epistaxis was significantly higher in group B compared to group A (p<0.001). The cut-off values to reveal the distance at which difficulty may be experienced while advancing the tube, determined through receiver operating characteristic analysis, were 1.09cm for vertical and 0.39cm for horizontal distances. Conclusion: The nasotracheal intubation procedure under the guidance of computed tomography could help predict the difficulty of tube advancement, and could thus prevent epistaxis and other related nasal intubation complications. Clinical trial number: NCT05525754. Key Words: Tomography, X-Ray Computed, Epistaxis, Orthognathic surgical procedures, Intubation.